Types Of Speech Act Performed By Private In The Movie "Penguin Of Madagascar" - Nanang Chusnul Ma'arif (JournEEL, 2022)
This purpose of this research is to identify and elaborate the speech acts that are utilized in the animated movie Penguin of Madagascar to the understanding of language function, alongside to point out the manifestation of speech acts adoption either in the real life or fiction dialogues. This study employed qualitative approach in which the research object contained the dialogues in the movies. The data were collected from an observation which is done by watching Penguin of Madagascar and then were distinguished Private dialogues according to the speech act distinguishment. The research outcome refers to the result that there are myriads of speech acts functions in the movie which applied from the language functions. The acts of speech itself were classified into expressive, representative, directive, commissive, declaration. The implementation of acts of speech functions is done by utilizing the dialogues of Private inside Penguin of Madagascar as a tool to manifest the language function and manifestation to the speech acts itself.